Environmental markets : a property rights approach - Anderson, Terry L. (Terry Lee), 1946-; Libecap, Gary D. (Cambridge : Cambridge University Press, 2014)
Environmental Markets explains the prospects of using markets to improve environmental quality and resource conservation. No other book focuses on a property rights approach using environmental markets to solve environmental problems. This book compares standard approaches to these problems using governmental management, regulation, taxation, and subsidization with a market-based property rights approach. This approach is applied to land, water, wildlife, fisheries, and air and is compared to governmental solutions. The book concludes by discussing tougher environmental problems such as ocean fisheries and the global atmosphere, emphasizing that neither governmental nor market solutions are a panacea.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Environmental economics; Environmental quality; Right of property -- Environmental aspects; Environmentalism -- Economic aspects